NADPH oxidases: Current aspects and tools - Katrin Schröder (Redox Biology, 2020)
Reactive oxygen species (ROS) have been shown or at least suggested to play an essential role for cellular signaling as second messengers. NADPH oxidases represent a source of controlled ROS formation. Accordingly, understanding the role of individual NADPH oxidases bears potential to interfere with intracellular signaling cascades without disturbing the signaling itself. Many tools have been developed to study or inhibit the functions and roles of the NADPH oxidases. This short review summarizes diseases, potentially associated with NADPH oxidases, genetically modified animals, and inhibitors.